A educação física e as dimensões do conhecimento na BNCC: um estudo a partir dos planos do ensino dos professores de uma rede municipal de ensino - Vidotti, Pedro Henrique Carbone (Universidade Federal de São Carlos, 2020)
The National Common Curricular Base (BNCC) approved in 2017 aims to promote changes in the curricula of the education system and schools in the country, stimulating the development of essential learning. Besides that, in the Physical Education discipline, one of the novelties is the inclusion of the eight dimensions of knowledge: Experimentation, Use and Appropriation, Fruition, Reflection on Action, Construction of Values, Analysis, Understanding, and Community Protagonism. Therefore, the purposes of this research are: a) to build an understanding of the Dimensions of Knowledge; b) to identify how they are already approached by teachers and c) to analyze and propose, together with teachers, what are the pedagogical possibilities of this concept. The research has a qualitative approach with interpretive description characteristics, employing documentary research and rounds of conversation as the data collection technique. The National Common Curricular Base and 17 didactic sequences from 8th and 9th grades designed by Physical Education teachers from a municipal education system were analysed. The round of conversations was composed of 32 teachers and the coordinator of the discipline of the education system. The information collected was classified into two categories, namely: Dimensions of Knowledge, at which each group of knowledge was prominently discussed, and Echoes, that sought to identify and interpret the participants' positions regarding the implementation of the base and the Dimensions of Knowledge. In the 17 didactic sequences analysed, were found 97 learning expectations that indicate the Construction of Values, Analysis and Understanding, and the moderation concerning Use and Appropriation, Fruition and Community Protagonism. At the National Common Curricular Base, in the 21 skills described for the 8th and 9th grades, there was a more eminent balance between the dimensions and the thematic units. We considered that the Dimensions of Knowledge are concrete possibilities to know, practice, appreciate, democratize access, develop values and understand the operation and the social aspects of bodily practices; therefore, are didactic tools for the discipline teachers to build their pedagogical proposals.
The physical education and the dimensions of knowledge: a study from the teaching plans of a education municipal network
Keywords: BNCC; Educação física escolar; Dimensões do conhecimento; Scholar physical education; Dimensions of knowledge; CIENCIAS DA SAUDE::EDUCACAO FISICA